Screen-printed carbon electrodes for the detection of boldenone - Kaur, R. (Trans Tech Publications Ltd, 2014)
Boldenone (androsta-1,4-dien-17-ol-3-one), an androgenic anabolic steroid (AAS), is intensively used for growth promoting purposes in animals for meat production and as a performance enhancer in athletics. Its use is prohibited either in animals intended for human consumption or directly for humans, as most of the anabolic steroids are completely metabolized. The current method of detection, such as the mass spectrometry coupled with gas chromatography or liquid chromatography are sensitive, highly specific and are popular methods of detection. However, these have some intrinsic drawbacks such as the requirements of complicated and expensive instrumentation, time consuming and production of narrow detection limits. Boldenone and its metabolites in urine samples of animal matrices can be detected by means of electrochemical methods using tunable and chemically-modified screen-printed carbon electrodes (SPCEs). Â© 2014 Trans Tech Publications, Switzerland.